Severe menopausal symptoms associated with reduced adherence to antiretroviral therapy among perimenopausal and menopausal women living with HIV in Metro Vancouver. Issue 5 (May 2018) - Duff, Putu K.; Money, Deborah M.; Ogilvie, Gina S.; Ranville, Florence; Kestler, Mary; Braschel, Melissa C.; Pick, Neora; Shannon, Kate
Abstract: Objectives: Although more women living with HIV (WLWH) are entering midlife, the experiences of perimenopausal and menopausal WLWH, including the effects of menopausal symptoms severity, remain understudied. This study longitudinally investigated the correlates of antiretroviral therapy (ART) adherence among perimenopausal and menopausal WLWH from Metro Vancouver. Methods: Analyses drew on longitudinal data (2014-2017) from Sexual health and HIV/AIDS: Women's Longitudinal Needs Assessment, an ongoing community-based cohort of WLWH, aged 14+, from Metro Vancouver, Canada. At baseline and biannually, participants completed an interviewer-administered questionnaire. Bivariate and multivariable logistic regression with generalized estimating equations were used to identify the correlates of self-reported <95% ART adherence. Results: The sample included 109 perimenopausal and menopausal WLWH (233 observations), with a median age of 49 years (IQR 44-53). Whereas most (68.8%) participants experienced menopausal symptoms, only 17% had received treatment (eg, antidepressants, hormone therapy) at baseline. In multivariable analysis, severe menopausal symptoms (adjusted odds ratio [AOR] 1.03, 95% confidence interval [CI] 1.00-1.06), injection drug use (AOR 2.86, 95% CI 1.44-5.55), and physical/sexual violence (AOR 2.33, 95% CI 1.02-5.26) independently and positively correlated with <95% adherence. Conclusions: These findings suggest that menopausal symptoms may undermine ART adherence, with overlapping vulnerabilities such as injection drug use and sexual/physical violence further exacerbating poor ART adherence. Women-centred, trauma-informed care approaches to detect menopause and treat menopausal symptoms are urgently needed. Such approaches should holistically address the intersecting barriers to adherence and link WLWH to peripheral health and social services, including trauma counseling and evidence-based harm reduction services.